2007
DOI: 10.2106/jbjs.f.00379
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Entry Compared with Medial and Lateral Entry Pin Fixation for Completely Displaced Supracondylar Humeral Fractures in Children

Abstract: Therapeutic Level I. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
145
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 23 publications
12
145
0
9
Order By: Relevance
“…There were no poor results, while cases treated with lateral pinning showed 74 % excellent and 26 % good results with no poor results. Similar results were shown by Kocher et al [2], Mostafavi and Spero [22], and Aronson and Prager [23]. The difference in functional outcome between the two groups in our study was not statistically significant ( P  = 0.53).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There were no poor results, while cases treated with lateral pinning showed 74 % excellent and 26 % good results with no poor results. Similar results were shown by Kocher et al [2], Mostafavi and Spero [22], and Aronson and Prager [23]. The difference in functional outcome between the two groups in our study was not statistically significant ( P  = 0.53).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, the advantage of lateral entry pin fixation is avoidance of iatrogenic ulnar nerve injury, although the construct may be less stable biomechanically [2, 810]. A few studies reported that there is no significant advantage of cross pins in comparison to lateral pins [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Two further randomised controlled trials were performed by Gaston et al [26] and Kocher et al [27] looking at 104 and 52 patients, respectively. Although both extended the elbow to over 90 degrees prior to inserting the medial K-wire to avoid injury to the ulnar nerve, only Kocher et al made an incision over the medial epicondyle.…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques have been reported, but crossed pinning with postoperative immobilization is the preferred technique (Brauer et al 2007, Kocher et al 2007, Zamzam and Bakarman 2009). Iatrogenic injury to the ulnar nerve has been described in up to 20% of the cases treated with crossed pinning (Lyons et al 1998).…”
mentioning
confidence: 99%
“…Iatrogenic injury to the ulnar nerve has been described in up to 20% of the cases treated with crossed pinning (Lyons et al 1998). In addition, radial pinning may damage the radial and anterior interosseous nerve (Brauer et al 2007, Kocher et al 2007, Omid et al 2008). …”
mentioning
confidence: 99%